A dynamic geofencing and dwell-time validation system for secure attendance tracking in higher education: methodological proposal - Michael Favour Edafeajiroke; Amanda Eromosele Ekata (Computer Science and Information Technologies, 2026)
Accurate attendance tracking is vital for student engagement and academic integrity, yet traditional methods are prone to error and proxy attendance. While technological solutions like biometrics and QR codes exist, they often suffer from high costs, privacy concerns, and an inability to verify continuous presence. This study proposes a dynamic geolocation-based attendance system to address these gaps. Developed with Flutter and Node.js, the system employs lecturer-defined geofences and a dwell-time validation rule, confirming attendance only if a student remains within the designated area for at least 80% of the class duration. It features cross-platform accessibility, role-based dashboards, real-time notifications, and exportable reports. The methodology followed an Agile approach, focusing on user-centered design and robust backend development. The resulting system offers a cost-effective, scalable solution that enhances accuracy, prevents proxy attendance, and supports the digital transformation of higher education administration.